Academic Culture Speechlessness in English Language Learning: A Narrative Inquiry into Freshmen's Challenges and Adaptation Strategies - Ramadhan, Firjatullah Putra; Khoirul Huda; Buyun Khulel (Jurnal Ragam Pengabdian, 2026)
This study describes the experiences of first-year students related to academic culture silence in English language learning during their transition from high school to university. The study was carried out in the English Education Department of Islamic Darul Ulum University Lamongan, Indonesia, and involved four students (two males and two females). The results show that students experienced diverse difficulties, including contradictions in high school teacher-centered approach and university student-centered approach, extensive use of English during classes, great number of academic assignments, inability to follow lectures, and psychological obstacles like anxiety, fear of errors, low self-esteem, and social comparison. Nevertheless, the students managed to overcome the difficulties by applying different techniques such as self-study with materials and watching English videos, consulting with professors and graduate students, teamwork with peers in learning, vocabulary improvement and building self-confidence, and perception of mistakes as a natural part of the learning process. Based on the findings, it could be said that academic culture silence is not a permanent barrier, but only a transitional state, and that linguistic competence, independence, and socialization are crucial for successful adaptation. This study is important for understanding the experience of freshmen at EFL local.